Diagnosis and Therapy of Female Genital Malformations (Part 2). Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry Number 015/052, May 2019) - Oppelt, Peter; Binder, Helge; Birraux, Jacques; Brucker, Sara; Dingeldein, Irene; Draths, Ruth; Eckoldt, Felicitas; Füllers, Ulrich; Hiort, Olaf; Hoffmann, Dorit; Hoopmann, Markus; Hucke, Jürgen; Korell, Matthias; Kühnert, Maritta; Ludwikowski, Barbara; Mentzel, Hans-Joachim; mon OʼDey, Dan; Rall, Katharina; Riccabona, Michael; Rimbach, Stefan; Schäffeler, Norbert; Shavit, Sandra; Stein, Raimund; Utsch, Boris; Wenzl, Rene; Wieacker, Peter; Zeino, Mazen (Geburtshilfe und Frauenheilkunde, 2021)
Objectives Female genital malformations may be present in the form of individual entities, they may involve neighboring organs or they may occur in the context of complex syndromes. Given the anatomical structures of the vulva, vagina, uterus and uterine appendages, the clinical picture of malformations varies greatly.Methods This S2k-guideline was developed by representative members from different medical specialties and professions as part of the guidelines program of the DGGG, SGGG and OEGGG. The recommendations and statements were developed and voted on using a structured consensus process with neutral moderation.Recommendations This guideline is the first comprehensive summary of female genital malformations from infancy to adulthood which covers clinical examinations, diagnostic workups and treatment options. Additional chapters have been included on complex urogenital malformations, vascular malformations, psychosomatic care, and tumor risk.Ziele Weibliche genitale Fehlbildungen treten z. T. singulär, organübergreifend oder im Zusammenhang mit komplexen Syndromen auf. Unter der Berücksichtigung der anatomischen Strukturen von Vulva, Scheide, Uterus und Adnexen kann sich die Fehlbildung in unterschiedlichsten klinischen Bildern darstellen. Je nach Ausprägung der Malformation können auch Organe des harnableitenden Systems oder assoziierte Malformationen mit einbezogen sein.Methoden Diese S2k-Leitlinie wurde durch repräsentative Mitglieder verschiedener Professionen im Leitlinienprogramm der DGGG, SGGG und OEGGG entwickelt. Die Empfehlungen und Statements wurden in einen strukturierten Konsens unter neutraler Moderation abgestimmt.Empfehlungen In der Leitlinie werden erstmals weibliche genitale Fehlbildungen vom Säugling bis hin zur adulten Frau gemeinsam in Klinik, Diagnostik und Therapieoption abgehandelt. Weiter wurden Kapitel bez. komplexe urogenitale Fehlbildungen, Gefäßmalformationen, psychosomatische Begleitung und das Tumorrisiko mit aufgenommen.
Keywords: guideline; genital malformations; subseptate uterus; septate uterus; bicornuate uterus; unicornuate uterus; malformations of the uterine adnexa; uterine vascular malformations